The Paradox of Personalization: A Critical Analysis of AI's Impact on Student Cognitive Development and the 'Illusion of Learning' in K-12 Education - Erry Hendriawan; Bahmid Hasbullah; Muh.Safar; Dina Mayadiana Suwarma; Muhammad Arsyad (PT Inovasi Pratama Internasional, 2026)
The rapid integration of artificial intelligence (AI) into K-12 education, particularly through personalized learning platforms, promises to tailor instruction to individual student needs, enhancing efficiency and engagement. However, this study critically examines an underexplored paradox: while AI-driven personalization offers immediate cognitive support, it may inadvertently undermine deeper cognitive development by fostering an “illusion of learning”—a state where students perceive competence without genuine understanding. Employing a qualitative multi-case study design across five Indonesian K-12 schools that extensively use AI-powered personalized platforms, this research gathered data through semi-structured interviews with 20 teachers and 60 students, classroom observations, and document analysis. Thematic analysis revealed five core themes: (1) surface engagement with content, (2) dependence on instant feedback, (3) erosion of problem-solving persistence, (4) metacognitive misalignment, and (5) teacher mediation as a mitigating buffer. Findings indicate that the very features designed to personalize learning—hints, step-by-step solutions, and adaptive scaffolding—can displace critical cognitive processes such as productive struggle, deep reasoning, and self-regulated reflection. Students frequently exhibited overconfidence in their learning, as measured by discrepancy between self-perceived mastery and performance on transfer tasks. The study articulates the “personalization paradox” wherein systems optimized for immediate learning outcomes inadvertently attenuate the cognitive struggle essential for long-term intellectual growth. Implications call for a recalibration of AI pedagogy toward “desirable difficulties” and collaborative human-AI orchestration to safeguard cognitive development in technology-rich classrooms